2021
DOI: 10.1186/s12879-021-06800-6
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus infection in Nigeria: a systematic review and meta-analysis of data published between 2010 and 2019

Abstract: Background Hepatitis B virus (HBV) is an infectious disease of global significance, causing a significant health burden in Africa due to complications associated with infection, such as cirrhosis and liver cancer. In Nigeria, which is considered a high prevalence country, estimates of HBV cases are inconsistent, and therefore additional clarity is required to manage HBV-associated public health challenges. Methods A systematic review of the literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 79 publications
(47 reference statements)
4
25
1
Order By: Relevance
“…28,41,47,55,56 This reflects the endemicity of HBV, high infectivity rate and its ability to survive for prolonged periods outside the body. 57,58 Despite the fact that some studies in Africa have shown a higher prevalence of HBV and HCV among patients with SCD, [59][60][61] we did not corroborate this in our study. Studies in Nigeria which compared the seroprevalence rates of HBV and HCV among patients with SCD, with and without a history of transfusion with healthy age-and sex-matched controls, did not show a significant difference in prevalence rate of these viral markers among both groups.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…28,41,47,55,56 This reflects the endemicity of HBV, high infectivity rate and its ability to survive for prolonged periods outside the body. 57,58 Despite the fact that some studies in Africa have shown a higher prevalence of HBV and HCV among patients with SCD, [59][60][61] we did not corroborate this in our study. Studies in Nigeria which compared the seroprevalence rates of HBV and HCV among patients with SCD, with and without a history of transfusion with healthy age-and sex-matched controls, did not show a significant difference in prevalence rate of these viral markers among both groups.…”
Section: Discussioncontrasting
confidence: 80%
“…Among blood donors in Nigeria, seroprevalence rates of HBV range between 2.0% and 10% 28,41,47,55,56 . This reflects the endemicity of HBV, high infectivity rate and its ability to survive for prolonged periods outside the body 57,58 …”
Section: Discussionmentioning
confidence: 99%
“…In 1982, a safe and effective vaccine that offers 90-100% protection against the HBV was discovered [16,17]. Following this, hepatitis B vaccination continues to be a part of the WHO Extended Programme for Immunization [18]. This underlines the need for HCWs who are exposed to the HBV infection on daily bases to be vaccinated against the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the Nigerian North-South dichotomy in the etiology of UGIB is not immediately clear; it could be that the burden of CLD is more in the north than in the south of Nigeria. A recent systematic review and meta-analysis showed that, where adequate data were available, hepatitis B seroprevalence is generally higher in the northern states of Nigeria than in the southern states [ 25 ]. Differential access to treatment of chronic infectious hepatitis and schistosomiasis could also play a role.…”
Section: Discussionmentioning
confidence: 99%